ISLAM DAN MEDIA MASSA - Waryani Fajar Riyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2013)
The arising terminological issues of communication in Islam have led to the different views in the perspective of science (science of communication). Generally, this study will clarify the relationship between Islam and the Mass Media, which, according to another term, is also called the linkage between Religion and Science (Science of Communication). To examine such interrelated links, the writer uses the triangulation method of Toshihiko Izutsu on the relationship between parole, speech, and langue. This is, in the term of Qur'an Communication is called linkage between kala>m (saying), qaul (words), and lisa>n (tongue). The conclusion is, the writer offers a model of Pro(f)ethics of Mass Media, between the values ​​of divinity, humanity, and culture. If it is viewed in the Prophetic Social Sciences (ISP) perspective, the three were identical to the values ​​of transcendence (God / Kala>m), humanization (human/qaul), and liberation (cultural communities /lisa>n).